Overview of structural, electronic, elastic, thermal, optical, and nuclear properties of Zr2AC (A= Al, Si, P, S, Ge, As, Se In, Sn, Tl, and Pb) MAX phases: A brief review - Dumooa R. Hussein; Khalid K. Abbas; Ahmed M.H. Abdulkadhim Al-Ghaban (Heliyon, 2023)
The Zr2AC MAX phases are a family of ternary carbides ceramics that possess layered structures and exhibiting exceptional properties resulting from combining the most desirable features of metals and ceramics. In addition, the Zr2AC MAX-phases exhibit numerous physical and chemical properties due to their chemical and structural characteristics, a tendency for multiple basal dislocations and exhibiting mobility under ambient conditions. This review extensively analyzes the properties of the Zr2AC MAX phase, as they are closely linked to the exceptional and potential applications of the MAX phase. For the first time, the present study analyzed various properties of Zr2AC MAX phases, including structural, electronic, elastic, thermal, optical, self-healing, nuclear, oxidation, and corrosion characteristics. Furthermore, this review included experimental and theoretical work with comparison. It's found that the Zr2AC lattice parameters a and c are deviations theoretically from 0.1 to 2% and 0.15–2.87% compared with experimental work. Also, the Zr2AC MAX phases are metallic characters and the conductivity differs depending on the type of the Zr2AC(different A element) MAX phases. Its concluded that the Zr2AC MAX phases are stiff, isotropic elastic properties and high machinability with damage tolerance and hardness levels ranging from 3.5 to 13.02 Gpa. The Zr2AC MAX phases are also resistant to corrosion, thermal shock, and oxidation as well as lightweight. In addition, at elevated temperatures the transition from brittle to plastic behavior can be occurred in the Zr2AC MAX phase. The Zr2AC MAX phase's optical properties are anisotropic such as electrical conductivity and mechanical properties. This review study provides a comprehensive details assisting researches to deal with Zr2AC MAX phase potentially for different applications.